A Review on Production of Hydrogen from Renewable Sources and Applications for Fuel Cell Vehicles - Rohendi, Dedi; Rahmah, Dea; Yulianti, Dwi; Amelia, Icha; Sya'baniah, Nyimas; Syarif, Nirwan; Rachmat, Addy (http://dx.doi.org/10.31427/IJSTT.2018.1.2.5, 2018)
Hydrogen gas is an energy carrier that has many advantages, including energy density for high mass and environmentally friendly. Hydrogen can be produced from various sources by numerous methods. Hydrogen production from renewable sources is interesting, due to the sustainable and inexpensive supply of the raw materials. Among the sources of renewable raw materials for hydrogen production are water and biomass with various production methods. It consists of the electrolysis of water with acidic and basic conditions, as well as thermochemical and biochemical biomass conversion.